PENINGKATAN KUALITAS MAJELIS TAKLIM MELALUI PENDAMPINGAN MANAJEMEN DI DUSUN CARIKAN DESA RINGINANOM KECAMATAN TEMPURAN - Samaniyah, Safngatul Ngasris; Purwanto, Purwanto; Amin, Muhammad (Universitas Mataram, 2024)
This community service activity aims to improve the quality of the taklim assembly through management assistance carried out in Carikan Hamlet, Ringinanom Village, Tempuran District. The object or target of this service activity is the 40 women members of the Taklim Council in Carikan Hamlet, Ringinanom Village, Tempuran District. The stages carried out in this service activity are preparation, program implementation and evaluation. The mentoring activities carried out can improve the quality of the Taklim Council in Carikan Hamlet, Ringinanom Village, Tempuran District. Mentoring is not only a process of providing direct assistance or direction, but also forming active collaboration between the mentoring team and the Taklim Council management. More than just providing instant solutions, mentoring aims to strengthen the internal capacity of the Taklim Council so that they can be independent in managing activities and overcoming challenges that may arise in the future.